Treatment of More Than Moderate Ischemic Mitral Regurgitation in Patients Undergoing Left Ventricular Reconstruction - Xieraili Tiemuerniyazi; Yangwu Song; Hanping Ma; Fei Xu; Wei Zhao (Cardiology Discovery)
Objective:. While evidence-based clinical guidelines recommend chordal-sparing mitral valve replacement, rather than mitral valve repair, in patients with severe ischemic mitral regurgitation (IMR) undergoing coronary artery bypass grafting, there are no similar recommendations for patients undergoing left ventricular reconstruction (LVR). This study aimed to compare the clinical outcomes of mitral valve repair and replacement in patients undergoing LVR complicated by more than moderate IMR. Methods:. In this single-center cohort study, a total of 74 consecutive patients who underwent LVR and mitral valve surgery (repair group: 59; replacement group: 15), during the period from March 2000 to March 2021 at Fuwai Hospital (Beijing, China) were retrospectively enrolled. Survival rates were calculated with the Kaplan-Meier method and compared using the log-rank test. Univariate Cox analysis was performed to evaluate possible confounders, followed by adjustment in multivariate analysis. The primary outcome was survival free of major adverse cardiovascular and cerebrovascular events (MACCE). Results:. Median follow-up time was 59.4 months. Compared with mitral valve replacement, mitral valve repair was associated with increased risk of perioperative use of ventricular assist device (22.0% vs. 0, P = 0.045). There was no difference in overall survival (hazard ratio (HR), 1.10; 95% confidence interval (CI), 0.31–3.93; Plogrank = 0.888) and MACCE-free survival (HR, 1.54; 95% CI, 0.65–3.65; Plogrank = 0.319), even after multivariate Cox regression (HR, 1.35; 95% CI, 0.37–4.88; PCox = 0.646; and HR, 1.41; 95% CI, 0.57–3.44; PCox = 0.455, respectively). Furthermore, while no differences were observed in ejection fraction and left ventricular end-diastolic diameter on follow-up echocardiography, mitral valve repair was associated with an increased risk of recurrent mitral regurgitation (P = 0.041). Conclusions:. In patients undergoing LVR complicated by more than moderate IMR, both concomitant mitral valve repair and replacement can be successfully achieved with comparable overall and MACCE-free survival outcomes; however, mitral valve replacement may be superior to mitral valve repair for persistent correction of mitral dysfunction.